Severely threatening events and marked life difficulties preceding onset or exacerbation of multiple sclerosis. Issue 1 (January 1989) - Grant, I; Brown, G W; Harris, T; McDonald, W I; Patterson, T; Trimble, M R
Abstract : Information was obtained on stressful life circumstances, using the Life Events and Difficulties Schedule (LEDS) from 39 patients with early multiple sclerosis and 40 matched nonpatient volunteers. The proportion of multiple sclerosis patients who experienced marked life adversity in the year prior to onset of symptoms was significantly higher than for nonpatients in the year before interview (77% vs. 35%). The excess in marked life stress was most evident in the 6 months before onset. Such stressors might explain the timing of symptom exacerbation for some patients with multiple sclerosis, perhaps by perturbing an already unstable neuroimmunological system.